Study of the Durability Against Acid Sulfuric Attack and Accelerated Carbonation of Eco-Efficient Self-Compacting Concrete Blended with Marble Powder - Boukhelkhal, Aboubakeur; Benguit , Ammar; Lakhdar, Azzouz (International Journal of Integrated Engineering, 2025)
Reinforced concrete structures can suffer from numerous problems such as the aggressivity of the environment and the carbonation phenomena. The introduction of fine industrial by-products (FIB) can reduce the permeability and hence improve the concrete durability. Marble industry generates high quantity of fine residue (marble powder) that can be used as FIB to produce an eco-cement. In this concern, five self-compacting concrete (SCC) mixtures were prepared using a constant water to binder ratio of 0.40, one as reference mix and four containing marble powder as a partial replacement of ordinary Portland cement (OPC). The durability of SCC subjected to sulfuric acid attack and accelerated carbonation were assessed. X-Ray diffraction analysis (XRD) were carried out to identify the mineralogical composition before and after durability tests. The results have shown that the use of marble powder is beneficial to improve the resistance of SCC to acid sulfuric attack. However, the incorporation of marble powder seems to accelerate the carbonation of SCC specimens..